Smart Gas and Water Detector Monitoring System using Android Mobile Application - Mohd Ibrahim, Iffan Darwis; Zainal, Nurfarina (Evolution in Electrical and Electronic Engineering, 2021)
This study discusses a ‘Smart Gas and Water Detector Monitoring System using Android Mobile Application which detects gas leakage and overflow of water in FKEE laboratory. The main objective of this project is to create a real-time online monitoring system via a mobile application that is integrated with the gas and water detector. Gas detector sensor (MQ5), water detector (ultrasonic sensor), and WiFi module (ESP8266 NodeMCU) for connection between software and hardware were used in this project as it is affordable in price, good sensitivity, and easy to implement. The smart gas and water detector monitoring system is able to get gas level and water level readings from a mobile application. This project can allow the user to monitor remotely, avoid leakage of the gas and save more water from wastage